Family practice research in the African region 2020–2022 - Robert J. Mash; Klaus Von Pressentin (African Journal of Primary Health Care & Family Medicine, 2024)
Background: The African region produces a small proportion of all health research, including primary health care research. The SCOPUS database only lists the African Journal of Primary Health Care Family Medicine (PHCFM) and the South African Family Practice Journal (SAFP) in the field of family practice.